2021
DOI: 10.3389/fcell.2021.786728
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Signaling and Resistance to Cancer Therapy

Abstract: The transforming growth factor β (TGF-β) pathway, which is well studied for its ability to inhibit cell proliferation in early stages of tumorigenesis while promoting epithelial-mesenchymal transition and invasion in advanced cancer, is considered to act as a double-edged sword in cancer. Multiple inhibitors have been developed to target TGF-β signaling, but results from clinical trials were inconsistent, suggesting that the functions of TGF-β in human cancers are not yet fully explored. Multiple drug resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 167 publications
(227 reference statements)
0
64
0
1
Order By: Relevance
“…This suggests that TGF-β signaling changes during tumor progression from tumor suppression to tumor promotion. TGF-β has been found to induce tumor resistance to chemotherapy through multiple pathways [ 114 ]. For example, the miRNA-mediated activation of the TGF-β signaling pathway can increase DNA repair capacity, leading to tumor drug resistance [ 115 ].…”
Section: The Signaling Pathways In Tumor Drug Resistancementioning
confidence: 99%
“…This suggests that TGF-β signaling changes during tumor progression from tumor suppression to tumor promotion. TGF-β has been found to induce tumor resistance to chemotherapy through multiple pathways [ 114 ]. For example, the miRNA-mediated activation of the TGF-β signaling pathway can increase DNA repair capacity, leading to tumor drug resistance [ 115 ].…”
Section: The Signaling Pathways In Tumor Drug Resistancementioning
confidence: 99%
“…Despite the encouraging potential displayed by TGF-β-targeted drugs in a part of pre-clinical animal studies, the results from subsequent clinical trials of those drugs seem to be disappointing. The application of TGF-β inhibition strategies in patients with fibrosis is challenging due to the systemic effects of TGF-β and the complexity of cancer and fibrosis formation [ 227 ]. Firstly, although TGF-β cascades are commonly activated to contribute to pathological processes, the physiological function of TGF-β cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Data on TGFB expression was also equivocal. TGFβ signaling is often dysregulated in human cancer, with tumor suppressive function in premalignant and early-stage lesions and oncogenic effects in more advanced lesions ( Zhang et al., 2021 ). One study found TGFB mRNA levels to be decreased in tumors from OTRs ( P = 0.036) ( Kosmidis et al., 2010 ), whereas another showed TGFβ staining to be more intense among the RTR population ( P = 0.049) ( Gutiérrez-Dalmau et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%